Realizations of TH Sounds among University Students in Brunei - Nur Raihan, Mohamad; Wardina, Baharin (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2024)
This study investigates the different realizations of TH sounds in Brunei English among 31 local university students based on their pronunciations in a recorded reading task and five-minute interview. The study also attempts to compare the variations in TH sound realizations between female and male speakers to identify gender-based differences. The paper aims to discuss these variations by comparing its findings to previous studies of TH sounds in Brunei. The findings mainly support previous studies on TH sounds, particularly for initial voiced TH and medial and final TH sounds. However, the more remarkable occurrences of dental fricative [θ] in initial voiceless TH in tokens such as threaten and third contrasts with earlier reports stating more use of plosive [t] instead. Also, it is unclear from our data whether female speakers are leading in linguistic changes as there is insufficient data. Hopefully, this study will contribute to discussing sociolinguistic trends and the defining features of Brunei English to distinguish it from other varieties, such as Malaysian and Singapore English.